Lateral-torsional buckling capacity of Hybrid Double-I-Box Beams: A numerical approach. Issue 3 (February 2019) - Deepak, MS; Shanthi, VM
In this article, a parametric study on the lateral-torsional buckling performance of thin-walled cold-formed steel Hybrid Double-I-Box Beams through numerical analyses has been presented. These built-up beams have distinctive cross-section geometry; the presence of more section modulus at the flanges provides high resistance to flexural bending and the closed-box portion offers high stiffness to resist torsion and lateral buckling. Therefore, these beams can be used for longer spans. The nonlinear finite element analysis was performed using ABAQUS software. All the beams were modelled as ideal finite element models adopting simply supported boundary conditions and loads were applied as end moments. To acquire a large number of data, three varying parameters were considered namely, hybrid parameter ratio, that is, yield strength of flange steel to web steel (1.0, 1.3, 1.5 and 1.7); ratio of breadth to depth of the beam (4/6, 5/6, 6/6 and 7/6); and length of the beam (1.0, 2.5, 5.0, 10, 15, 20, 30, 40, 50 and 60 in m). The thickness of both the flanges and the webs were 2.5 mm. All these parameters alter the overall slenderness of the members. It is shown that at larger spans, Hybrid Double-I-Box Beams experience lateral buckling. The results obtained from the numerical studies were plotted on nondimensional moment versus nondimensional slenderness graph. These results were compared with the predictions using effective width method design rules specified in Euro codes EN 3-1-3 and buckling curve-d of EN 3-1-1, which was originally adopted lateral-torsional buckling capacities of hot-rolled steel 'I' sections, and the adequacy is checked. It was found that Hybrid Double-I-Box Beams has higher lateral-torsional buckling capacity than common 'I' or box sections. Hence, a new simplified design equation was proposed for determining lateral-torsional buckling capacity of Hybrid Double-I-Box Beams.